Arginine vasopressin deficiency after surgical ligation of an unruptured anterior communicating artery aneurysm – a case report and literature review - Gundersen, Julia K.; Holmøy, Anne Katrin Torsheim; Eide, Per Kristian; Winther, Jacob Andreas (Frontiers in Endocrinology, 2025)
IntroductionPlasma osmolality is maintained within a narrow range by secretion of arginine vasopressin (AVP). AVP deficiency (formerly known as central diabetes insipidus) is a rare complication of surgery in the hypothalamic and pituitary region.Case descriptionA 50-year-old male patient developed postoperative dehydration, polyuria and cognitive impairment following surgical clip ligation of an unruptured anterior communicating artery (ACOM) aneurysm. Endocrine tests revealed moderate hypernatremia, plasma hyperosmolality and urine hypoosmolality. Magnetic resonance imaging of the brain uncovered delayed cerebral infarctions in genu rostrum of corpus callosum and bilateral oedema of fornix anterior columns. All clinical findings supported the diagnosis of central AVP deficiency, likely involving the anterior hypothalamic nuclei. Follow-up 2 months postoperatively confirmed persisting AVP deficiency and cognitive impairment.ConclusionAVP deficiency without associated haemorrhage is exceedingly rare, with only seven cases identified in our literature review. This case highlights that postoperative AVP deficiency may present with mild or unspecific symptoms. Importantly, concurrent cognitive impairment may occur, further complicating compliance to treatment. Therefore, close postoperative monitoring is crucial for correct diagnosis and bed-side management.